Svilnica Cettia cetti - Gračner, Jože (Acrocephalus, 1991)
Caught at Lake Cerknica on 25th August 1990
Keywords: Birds; Cerkniško jezero; Cettia cetti; Martinjak; opazovanje; Ornithology; ornitologija; ptiči; Slovenia; Slovenija; svilnica